The Relationship Between Breast Care and Continuity of Mother’s Milk in Postnatal Care: Hubungan Perawatan Payudara dengan Kelancaran ASI pada Ibu Masa Nifas. - MARIA TAMBUNAN; Sherlia Sofiana; Febby Triani Pemalia (Politeknik Karya Persada Muna, 2022)
Baground : Breast feeding to baby is the best food supply, especially when the baby is at the age of 0-6 months. Mother’s milk is the most perfect food in which its nutrition suits for baby needs to grow optimally. Therefore, treatment for pregnant woman health particularly breast care is needed to be increased in order mother’s milk can be produced maximally. Method : This research aims at finding out correlation of breast care and continuity of mother’s milk in postnatal care. This was observational analytical research that applied quasi experimental approach. Population of this research was all women that were in postnatal care period. Sample was taken by total sampling technique that consisted of 36 of woman who were in postnatal care. The data of this research were analyzed by chi square test. Results : Based on the analysis, it is found that there is correlation of breast care and continuity of mother’s milk in postnatal care in which p value = 0,030 (p.value ,0,05) Conclusions : Based on the analysis, it is found that there is correlation of breast care and continuity of mother’s milk in postnatal care in Matahari ward of Undata General Hospital of Palu Keyword : Breast Care, continuity of mothers milk